Housing and Communal Services of Kyiv during the German-Soviet War Based on the Materials of the Occupation Press (September 1941 — September 1943) - Dmytro Kolomiiets (Київські історичні студії, 2023)
The article is dedicated to the state of housing and communal services in Kyiv as covered in the periodicals «Ukrainske Slovo», «Nove Ukrainske Slovo» and «Ostanni Visti» during the period of German occupation. Analysis of the newspapers' materials made it possible to outline the state of the housing stock and communal infrastructure from the entry of the occupying forces into the city until the end of the German administration's activities. The newspapers' pages contain information on statistical calculations of the destruction in Kyiv, as well as activities related to the localization and elimination of these consequences. The materials reveal propaganda cliches, distortion, and exaggeration of information regarding the state of affairs in housing and communal services. For the mentioned aspect, it is possible to reflect the common and distinct features of German propaganda in the periodicals used in all the territories where it was active. This includes the use of “soft power” by the occupying press to instill new political beliefs, friendliness towards Germans in the population of Kyiv. In particular, appealing to the destruction of housing and critical infrastructure of the city by the Soviets. Attention to the materials of the occupation press and their objective evaluation not only allows for determining the degree of distortion of the information provided in the context of the historical time reviewed but also in comparison with the activity of such presses in the modern world. Russian occupation administrations currently use the full spectrum of mass media, including the press, to distort reality and conduct political propaganda on temporarily occupied territories in Ukraine. In many respects, the occupiers adhere to similar or identical forms of the fascist regime of reflecting non-existent reality, including issues related to housing and communal services destroyed or damaged by themselves in the territories they occupy.